APLIKASI YUNIT LAUNDRY MENGGUNAKAN FRAMEWORK SCRUM - Marcelliano Riccardy Anantho Omega Kalitouw; Gladly C Rorimpandey S.T, MISD; Vivi P Rantung S.T, MISD (Program Studi Teknik Informatika, 2023)
The current development of smal and medium enterprise (MSMEs) is not accompanied by the application of information technology, which is increasingly developing rapidly. This is experienced by almost all laundry business actors in North Sulawesi. This study aims to develop the Yunit Laundry application which can support the operations of laundry entrepreneurs. On the other hand, it can help laundry service users in accessing laundry services or using laundry services. This study applies the Scrum framework as a guide in the system development process. Meanwhile, system modeling uses the Unified Modeling Language. The results of this research are a series of web site applications that will be used by laundry entrepreneur admins and Android-based mobile applications for laundry service users.